Hegemoni Politik Melalui Good Governance - Sunardi, Sunardi (Madika: Jurnal Politik dan Governance, 2023)
This article will look at the dynamics of the development of good governance in Indonesia. By using political hegemonic sub-districts, this article attempts to reveal the presence of good governance as something that does not just happen. This article tries to provide a different view from most of the views that have so far looked at the development of good governance in Indonesia. By relying on literature studies, this article argues that good governance in Indonesia provides benefits, although at a not too large a level. But at the same time, good governance offers a recipe for apolitical governance. Attempting to avoid political involvement nuanced conflict. Thus this article views conceptually, that good governance as a concept is a political instrument. Good governance as an instrument to hegominate the implementation of governance in Indonesia.